RISK FACTORS FOR NEONATAL SEPSIS IN NEONATAL INTENSIVE CARE UNIT: EVIDENCE STUDY - Cecília Olívia Paraguai de Oliveira; Juliana Raquel Silva Souza; Regimar Carla Machado; Alexsandra Rodrigues Feijão; Nilba Lima de Souza (Universidade Federal do Paraná, 2016)
Integrative literature review aimed to present the main evidence of risk factors for neonatal sepsis in newborns admitted to a Neonatal Intensive Care Unit. The search was performed between the months of July and August 2015, in the databases Scientific Electronic Library Online, SciVerse Scopus and PubMed, using the following descriptors: risk factors, neonatal intensive care unit, newborn and the following keywords: neonatal sepsis and prematurity. The search included 31 publications whose outcomes showed that the predictive factors for neonatal sepsis are associated to gestational age, premature rupture of amniotic membranes and maternal infection. Birth conditions, low weight and prematurity are strong evidence of sepsis. The factors related to the environment of the neonatal intensive care unit are potential contributing factors associated to late-onset sepsis.